MEAgriSys - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2007)
MEAgriSys: An Integrated Monitoring and Evaluation (ME) Agrcultural(AGR)Information(II)System (SYS) for Measuring Progress and Impact of Development Actions to improve the Agri-Food Sector and Rural Life